Cluster-enabled patterning of copper nanostructures from aqueous solution using a femtosecond laser. (26th September 2022) - Luo, Zhijun; Zeng, Zhihao; Liu, Ziyu; Wang, Duan; Gan, Zongsong; Xie, Changsheng
Abstract: A one-step method for patterning low-resistivity nanoscale copper wire is proposed herein to solve the challenging issues of using common metals rather than noble metal nanostructures fabricated by direct laser writing in solution. A complexing and a reducing agent were introduced for the single-photon absorption of copper solution in the visible range and to enable two-photon absorption with a femtosecond laser. Copper clusters were generated prior to direct laser writing to decrease induced laser energy during two-photon absorption and accelerate copper nanowire patterning to avoid the boiling of copper solution. A surfactant was used to restrain the overgrowth of copper clusters to obtain written nanowires with high uniformity. By controlling the laser writing parameters, the obtained copper wire had a minimum width of 230 nm and a resistivity of 1.22 × 10 −5 Ω·m. Our method paves the way for the fabrication of common metal nanodevices by direct laser writing.